Analisis Laporan Keuangan Dana Desa Pada Kampung Sri Sawahan Kecamatan Punggur - Nani Septiana; Deny Edy Widodo; Muhammad Rafli (Universitas Muhammadiyah Metro, 2024)
Financial statements are information that describes the condition of a company ororganization which will then become information that describes the performance of acompany or organization. This research was conducted to analyze the financial reports ofvillage funds with the aim of assessing the performance of village government apparatususing village income and expenditure reports in the 2020 and 2021 fiscal years. In this studythe ratios used were the regional independence ratio and the regional spending efficiencyratio. This study uses a descriptive method with a quantitative approach. The object of thisresearch is Sri Sawahan Village, Punggur District. The data in this study used villagerevenue and expenditure budget data (APBDes) in the 2020 and 2021 fiscal years. Theresults of the research are that the performance of the government of Kampung Sri Sawahanin terms of regional independence ratio in 2020 and 2021 is very low. And the regionalspending efficiency ratio also shows less efficient results.